SEMANTIC ANALYSIS OF MEANING IN THE MIRROR POETRY ANTHOLOGY BY HADI MULYADI - Amalia Firda Fahraniah; Putri Aulia Alpin; Fikri Hakim (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research analyzes the language style in the poetry anthology "Cermin" by Hadi Mulyadi 2020, focusing on contradiction, comparison and repetition. Conflicting language styles are represented by hyperbole and paradox. Hyperbole is used excessively to express the beauty of orchids, the sincerity of dew, and the durability of advice. Paradox arises in the complexity of the word "sincerity," the beauty of a woman from the love of another, and the contradiction of the silence of the soul with the anxiety of waiting. Comparative language style enriches poetry through metaphor, personification, comparison (simile), allegory, and simile. Metaphor associates advice with snow, personification gives human qualities to objects, allegory depicts a monotonous and lonely life through a house without windows, flowers and sounds. The simile is used to compare friends to rain, emphasizing blessings. The repetitive language style is present through alliteration, with the repetition of consonant sounds at the beginning of words. Although the parallelism is not striking, alliteration gives rhythm to the poem. This research highlights the rich meaning and beauty of Hadi Mulyadi's contemporary poetry, showing that "Cermin" is not just a medium for conveying the meaning of words, but a work of art that depicts the complexity and beauty of language